Penyuluhan Hukum Tentang Peranan Alat Bukti Persangkaan di Lingkungan Gatep Permai Kelurahan Taman Sari Kecamatan Ampenan Kota Mataram - Mualifah Mualifah; Ridwan Ridwan; Lewis Grindulu (Universitas Mataram, 2022)
A proof by law is essentially a process of determining the substance or essence of the existence of facts obtained through a reasonable measure with a logical thought of the facts of the past which are not clear to be clear facts in relation to the matter examined. Therefore, we conducted legal counseling on the role of evidence of suspicion in the beautiful gatep environment of Taman Sari sub-district, Ampenan sub-district, Mataram City. Which aims to spread widely about the importance of evidence in civil matters especially in the settlement of civil cases which should include evidence of suspicion in evidence as a means or tool to resolve a matter that is key and very important and decisive in resolving civil cases in addition to improving knowledge and awareness of the law in society. The method used in this extension activity is to use the method of lectures and discussions. So it is hoped that participants can better understand the material presented. The target audience for this activity is students, village youths and the general public in the area of Gatep Permai. Based on the results of the evaluation conducted by the counselor after the completion of this counseling activity in general can be said that the new participants know the material presented, due to the lack of knowledge of participants about the role of evidence of suspicion.